Estudo do comportamento autonômico cardíaco e do acoplamento cardiorrespiratório em pacientes portadores da Síndrome da Apnéia Obstrutiva do Sono: efeitos da obesidade e do envelhecimento - Trimer, Renata (Universidade Federal de São Carlos, 2014)
The thesis consisted of three studies described below. The Study I, entitled: Is there a chronic sleep stage-dependent linear and nonlinear cardiac autonomic impairment in obstructive sleep apnea? The aim of this study was to perform HRV analysis in apneafree samples as well as during stage 2 and rapid eye movement (REM) sleep in mild and moderate OSA (MiOSA andMOSA,respectively) subjects as well as health controls (NonOSA). Methods This study included 20 MiOSA (37±14 years), 20 MOSA (39±8 years), and 18 NonOSA (36±8 years) subjects. Subjects underwent in-laboratory overnight polysomnography with electrocardiography recording. HRV indices were obtained by analyzing the R R intervals (RRi) in 5-min apnea-free samples by the linear frequency domain [low frequency (LF), high frequency (HF) and LF/HF], Poincaré plot [standard deviation (SD1) and (SD2)], recurrence plot [mean line length (Lmean)], recurrence rate (REC), determinism (DET), and Shannon entropy (ShanEn). The MOSA group presented with higher LF, LF/HF and DET indices compared to NonOSA as well as a lower parasympathetic index (HF), suggesting sympathetic hyperactivity in MOSA subjects. Interestingly, MiOSA subjects failed to show the expected linear HRV difference between sleep stages, as observed in NonOSA, which may represent an early onset of autonomic impairment at this stage of OSA. In OSA patients, there is a chronic sleep stage dependent impairment of linear and nonlinear cardiac autonomic modulation. Interestingly, this impairment may be identifiable during the early stages of the disease. The Study II, entitled: Heart Rate Variability and Cardio-Respiratory Coupling during sleep in Patients prior to Bariatric Surgery The aim of this study was to determine the relationship among severity of obesity, autonomic cardiac regulation, respiratory variations, and cardio-respiratory coupling during different sleep stages (SS), using spectral analysis of HRV and respiration variability (RS) signals in patients pre-operative BS. 29 consecutive pre-operative BS and ten eutrophic subjects (controls) underwent polysomnography. The spectral and cross-spectral parameters of the HRV and RS were computed during different SS. Spectral analysis of the HRV and RV indicated lower respiration regularity during sleep, and a lower HRV in obese patients (OP) during all SS when compared with controls (p<0.05). Severely (SO) and super obese patients (SOP) presented lower values of LF/HF ratio and LF power during REM sleep and higher HF power (p<0.05), while morbidly obese (MO) presented lower LF/HF ratio and LF power in SS-S2 and higher HF power when compared to controls (p<0.05). The cross-spectral parameters showed that SOP presented lower % of tachogram power coherent with respiration in SS-S3 when compared to controls (p<0.05). Patients prior to BS presented altered HRV and RV in all SS. SO, MO and SOP presented altered cardiorespiratory coupling during sleep and these alterations are related with severity of obesity and OSA parameters. Our third study entitled "Contrasts of heart rate variability and cardio respiratory coupling in young and elderly patients with OSA", aimed to contrast the impact of OSAS between young and old in HRV and CRC. It also seeks to establish whether age impacts differently on HRV and CRC during different sleep stages using spectral analysis of HRV and RV in young and elderly patients with and without OSA. The spectral analysis of HRV showed that the presence of OSA negatively impacted on HRV youth, with higher values of LF/HF (p <0.05) during wakefulness and different sleep stages with lower values of LF/HF during S2 and REM sleep (p <0.05). We also observed that age negatively affected HRV during wakefulness and sleep in elderly with higher LF/HF during waking. Young and old with OSA had significantly lower % of tachogram power coherent with respiration only during wakefulness (p <0.05). The presence of OSA has a negative impact on HRV in young and elderly, with reduced autonomic modulation during waking and REM sleep. Age has a negative impact on HRV during wakefulness and sleep in the elderly. The presence of OSA and age affect negatively the ACR during wakefulness.
Keywords: Fisioterapia; Síndrome das apnéias do sono; Variabilidade da frequência cardíaca; Obesidade; Envelhecimento; Acoplamento cardiorrespiratório; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL